The Undergraduate Learners' Perspective on Listening Comprehension of Audio-Lingual Transcript Method at The Fourth Semester Student’s University of Muhammadiyah Makassar - Rukmayana, Wika; Syatriana , Eny; Zia Ul Haq, Muhammad (FKIP Unismuh Makassar, 2020)
This study aims to determineTo find out the perspective of fourth semester students at Muhammadiyah Makassar University in listening to audio-lingual transcripts.The method that will be used by the researcher is a qualitative descriptive approach because This study wants to describe the perspectives of fourth semester students at the University of Muhammadiyah Makassar.The subjects of this research are fourth semester students who have participated in learning English listening comprehension using the audio lingual method as many as 21 students in class 4A. However, the researcher only took a sample of 15 students to be studied at the Muhammadiyah University of Makassar. Samples were taken using a questionnaire with Google forms. The results showed thatFrom the results of research that has been carried out with a questionnaire totaling fifteen statements, it is known that the majority of respondents choose the category of agree or good in learning English using the audio-lingual transcription listening method or it can be said that the fourth semester students of the English Education Study Program prefer the method of learning English. listening audio-lingual transcripts in the learning process at the University of Muhammadiyah Makassar.